Does collaboration pay in agricultural supply chain? An empirical approach. Issue 13 (3rd July 2018) - Despoudi, Stella; Papaioannou, Grammatoula; Saridakis, George; Dani, Samir
Abstract : This paper examines the effect of different types of collaboration on the level of Postharvest Food Losses (PHFL) and the proportion of low-quality peaches produced using a unique data-set of Greek peach producers. Quantile regression techniques are adopted to estimate the effects at different points of the conditional distribution of our variables of interest. The findings of this study suggest that high levels of collaboration between producers and cooperatives are associated with both low levels of PHFL and a low proportion of low-quality peaches. We also find that specific types of collaboration, such as 'goal congruence', can play a significant role in reducing PHFL and improving the quality of peach production at the extremes of the distribution. Important policy implications regarding collaborative practices and systems that can be implemented to reduce PHFL and boost a producer's performance together with sustainability credentials are drawn from this study.